Comparative Evaluation of Permissiveness to Dengue Virus Serotype 2 Infection in Primary Rodent Macrophages - Jeanette Prada-Arismendy; Verónica Rincón; Jaime E. Castellanos (Journal of Tropical Medicine)
Infection with dengue virus presents a broad clinical spectrum, which can range from asymptomatic cases to severe cases that are characterised by haemorrhagic syndrome and/or shock. The reason for such variability remains unknown. This work evaluated the in vitro permissiveness of mouse, rat, hamster and guinea pig macrophages to infection by dengue virus 2 (DENV2). The results established that macrophages derived from the BALB/c mouse strain showed higher permissiveness to DENV2 infection than macrophages from other rodent species, although all rodent species studied had the C820T mutation in the oligoadenylate synthetase 1b gene, indicating no relationship to the different in vitro susceptibilities of mouse cells at this locus. Other molecular mechanisms related to flavivirus susceptibility remain to be explored.